Risk Factors for Hypertension in Women of Childbearing Age - Vidia, Natasya; Simanjuntak, Betty Yosephin; Nugraheni, Diah Eka (Poltekkes Kemenkes Tanjung Karang, 2023)
Hypertension can be triggered by a secondary cause, namely the use of hormonal contraceptives. Hormonal contraceptives contain the hormones estrogen and progesterone, resulting in a hormonal imbalance that leads to hypertension. This research aims to know the relationship between the duration of use and the type of hormonal contraceptives that can be associated with the incidence of hypertension. In Indonesia, the most common use of contraception is hormonal contraception (85.7%), including 139,342 injections (56.8%), 64,569 pills (26.3%), and 14,901 implants (6%). It is known that 216 out of 766 (28.19%) women of childbearing age who use hormonal contraceptives in the Telaga Dewa Health Center working area suffer from hypertension. Cross-sectional research design with a sample of 369 women of childbearing age. The type of hormonal contraception used, age, and blood pressure were obtained by secondary means from the midwife's register book. At the same time, primary door-to-door accepted length of use, education, employment, and number of children. It was found that the size of the use of hormonal contraceptives >5 years significantly related to the incidence of hypertension (p-value 0.000) with OR 2.685. The result will show how the relation of duration use and type of hormonal contraceptives can be associated with the incidence of hypertension. However, all types of hormonal contraceptives were not significantly related to the incidence of hypertension (p-value 0.223). The conclusion of the research is that age, occupation, education, parity, and use of hormonal contraception can be causes of hypertension in women of childbearing age.